Strategi Komodifikasi Budaya dalam Ritual Yaa Qowiyyu pada Masyarakat Jatinom, Klaten - Nur Quma Laila; Saifuddin Zuhri Qudsy (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
Yaa Qowiyyu as a religious ritual not only contains religious values but also full of economic-political values. This paper aims to find out how economic value runs in Yaa Qowiyyu ritual and how the strategies of agencies in promoting Yaa Qowiyyu bring economic value. Primary data in this article was collected by observations, interviews and documentation methods, while secondary data was collected through literature study. Political-economic perspectives are used to analyze the collected data. The results showed that the management of Yaa Qowiyyu ritual which was based on tourism policies had broad implications for the process of cultural commodification. The commodification of culture in Yaa Qowiyyu ritual is a secondary activity that is able to encourage the community's economy.